Higher Protein Density Diets Are Associated With Greater Diet Quality and Micronutrient Intake in Healthy Young Adults - Gwin, Jess A.; Karl, J. Philip; Lutz, Laura J.; Gaffney-Stomberg, Erin; McClung, James P.; Pasiakos, Stefan M. (Frontiers in Nutrition, 2019)
Objective: This study characterized habitual dietary protein intake in healthy young adults entering military service and explored whether diet protein density is associated with diet quality and micronutrient intake. Methods: An FFQ was used to estimate habitual dietary intake and HEI scores in 276 males (mean(SD), age:21.1y(3.8)) and 254 females (age:21.2y(3.7)). Multivariate-adjusted MANCOVA and ANCOVA models were used to identify associations between protein density quartiles and HEI scores and micronutrient intake. Higher HEI components scores for sodium, refined grains, and empty calories indicate lower intake; higher scores for all other scores indicate higher intakes. Results: Mean(SD) energy-adjusted protein intakes were 29.3(3.2), 36.0(1.4), 40.8(1.3), and 47.9(3.9) g/1000 kcal for protein density quartiles 1-4, respectively. For males, empty calorie scores as well as dark green and orange vegetable scores were higher in quartiles 3 and 4 than 1 and 2 (all, p<0.05). Scores for total vegetable, dairy, and total protein foods were lower in quartile 1 vs. quartiles 2, 3, and 4 (all,p<0.05). Sodium scores decreased as quartiles increased (p<0.001). Total HEI, fruit, whole grains, seafood and plant protein, fatty acids, and refined grain scores did not differ. For females, total HEI, vegetable, and total protein foods scores were higher in quartiles 3 and 4 than 1 and 2 (all,p<0.05). Empty calorie scores increased as quartile increased (p<0.05). Dairy scores were higher in quartiles 2, 3, and 4 than 1 (p<0.05). Whole fruit scores were lowest in quartile 1 (p<0.05). Whole grain as well as seafood and plant protein scores were higher in quartile 4 vs. 1 (both, p<0.05). Sodium scores decreased as quartile increased (p<0.001). Fatty acids scores did not differ. For males and females, micronutrient intakes progressively increased across quartiles with the exception of calcium and vitamin C, (all,p<0.05). Intakes remained nearly the same when controlled for fruit and vegetable intake. Conclusion: These cross-sectional data suggest that habitually consuming a higher protein density diet is associated with better scores for some, but not all, diet quality components in males, better overall diet quality scores in females, and greater intakes of micronutrients in both male and female adults entering military service.